KEJAHATAN TERHADAP KEMANUASIAAN DAN PELANGGARAN HUKUM HUMANITER INTERNASIONAL (Konvensi Jenewa 1949) Studi Kasus: Pelanggaran HAM Berat untuk Bekas Negara Yugoslavia - Mumtazinur Mumtazinur (Dusturiyah: Jurnal Hukum Islam, Perundang-undangan dan Pranata Sosial, 2018)
The article is an effort to explain violations of humanitarian law that occurred during the war in Yugolavia. It begins by a brief description of  international Humanitarian Law. This articles also describing he form of violations of Geneva conventions and forms of punishment against violators of humanitarian law. Besides, it also explain the form of punishment given by international criminal courts.